Aplikasi Spectrum Analyzer Untuk Menganalisa Frekuensi Sinyal Audio Menggunakan Matlab - Wahyudi, Septian Tri; safrianti, Ery; Rahayu, Yusnita (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
In this study, the authors implement an application Spectrum Analyzer used to examine the frequency response of the human voice. This application begins with making the function of the Fast Fourier Transform (FFT), which calculates the value of the amplitude of a wave file. Then the manufacture equalizer and normalization adjusts the value of the highest amplitude of each spectrum to be more easily studied. Spectrum Analyzer application is built using MATLAB programming language. From the test results, the human voice is in the frequency range of 300 -3400 Hz and a human voice shrill has higher frequencies then bass, By using sound recorder application that already include in the operation of windows, the audio signal will be at the input. The audio signal that we will process here is the type of audio signal stereo. Stereo signals having a phase of R and L which produces the dominant voice on the left or right.  Keywords : Fast Fourier Transform (FFT), the audio signal, spectrum analyzer